THE EFFECT OF KNOWING THE MAIN IDEA OF A TEXT ON ANSWERING MULTIPLE-CHOICE QUESTIONS WHICH LOOK FOR THE DETAILS OF THE TEXT - Merrikhi, Pegah (Jurnal Ilmiah Peuradeun, 2014)
This paper describes a classroom research with two groups of high school students to clarify the effect of knowing the main of a text (here, the name of a story) on answering multiple-choice questions which look for details. The two groups read the same story with an appropriate level of difficulty which was suitable for their level of English proficiency. The only difference between their stories was that one of them had the name of the story above it and the other did not have. Each group then took a reading comprehension test and their mean scores were compared. The findings suggest that the group of students who read the story with the name of it above did not excel the group who read the same story without its name when answering to questions looking for minute aspects of the story. This lack of excellence shows that knowing the main idea of a text does not play an important role in answering reading comprehension questions which look for details of a text. The results suggest more research in this realm and also the need for instruction on answering reading comprehension texts.